Mapping of radioactive contamination with predetermined confidence level - Yu. V. Khomutinin; S. E. Levchuk; V. P. Protsak; V. O. Kashparov (Ядерна фізика та енергетика)
Standard approaches to the construction of maps of radioactive contamination do not provide errors in map data, so such maps do not, in fact, guarantee the accuracy of the map information. In this paper, based on the fact that the characteristics of radioactive contamination at a particular point in the territory have a lognormal probability distribution, a methodology for creating maps with a guaranteed confidence level of the provided information has been proposed and tested. There are considered two ways of creating maps, based on the results of "direct" measurements of radioactive contamination characteristics and in the combination of "direct" and "indirect" measurements of values statistically related to the mapping characteristic. The approaches and use of kriging methods proposed in the article allow to create maps with a given level of confidence and, accordingly, to take into account the risks caused by the uncertainty of measurements of radioactive contamination characteristics and uncertainty of their approximation.